Parasitic loads in tissues of mice infected with Trypanosoma cruzi and treated with AmBisome. - Sabrina Cencig; Nicolas Coltel; Carine Truyens; Yves Carlier (PLoS Neglected Tropical Diseases)
Background Chagas disease is one of the most important public health problems and a leading cause of cardiac failure in Latin America. The currently available drugs to treat T. cruzi infection (benznidazole and nifurtimox) are effective in humans when administered during months. AmBisome (liposomal amphotericin B), already shown efficient after administration for some days in human and experimental infection with Leishmania, has been scarcely studied in T. cruzi infection. Aims This work investigates the effect of AmBisome treatment, administered in 6 intraperitoneal injections at various times during acute and/or chronic phases of mouse T. cruzi infection, comparing survival rates and parasitic loads in several tissues. Methodology Quantitative PCR was used to determine parasitic DNA amounts in tissues. Immunosuppressive treatment with cyclophosphamide was used to investigate residual infection in tissues. Findings Administration of AmBisome during the acute phase of infection prevented mice from fatal issue. Parasitaemias (microscopic examination) were reduced in acute phase and undetectable in chronic infection. Quantitative PCR analyses showed significant parasite load reductions in heart, liver, spleen, skeletal muscle and adipose tissues in acute as well as in chronic infection. An earlier administration of AmBisome (one day after parasite inoculation) had a better effect in reducing parasite loads in spleen and liver, whereas repetition of treatment in chronic phase enhanced the parasite load reduction in heart and liver. However, whatever the treatment schedule, cyclophosphamide injections boosted infection to parasite amounts comparable to those observed in acutely infected and untreated mice. Conclusions Though AmBisome treatment fails to completely cure mice from T. cruzi infection, it impedes mortality and reduces significantly the parasitic loads in most tissues. Such a beneficial effect, obtained by administrating it over a short time, should stimulate studies on using AmBisome in association with other drugs in order to shorten recovery from T. cruzi infection.